(untitled) (Al-Aasar, 2025)
The Quran is the most superior and final divine book revealed by Allah. It encompasses all religious and worldly matters that will arise until the Day of Judgment. While the Quran provides a complete code of life and guidance regarding beliefs and dealings, its words and recitations (Qirā’āt) are also a source of mercy. The Ahl al-Sunnah (People of the Sunnah) have a consensus that just as the Quran has been transmitted to us through an uninterrupted and authentic chain (Tawātur), the recitations (Qirā’āt) related to the Quran have also been transmitted in the same manner. However, due to the existence of different Qirā’āt, various schools of thought hold differing opinions. These schools of thought consist of some Islamic scholars, the Ash‘arites, the Mu‘tazilites, philosophers, certain Shia groups, and Orientalists, who interpret the Quran in their own ways. They have established principles to justify Quranic recitations according to their beliefs. Some individuals completely deny the concept of Qirā’āt, while others partially accept them, interpreting them to align with their theological doctrines. Additionally, some reject certain Qirā’āt because they appear to contradict their religious or ideological beliefs. This study, while analyzing the discussions on the differences in Qirā’āt, concludes that the variations in recitations do exist, but these differences are not contradictions; rather, they represent diversity in expression. This diversity does not alter the intended meaning of the Quran, and despite the variations in Qirā’āt, the essence of the message remains unchanged.